Al-Farabi's Socio-Political Philosophy and Implementation Towards Democracy - Agustina, Agustina; Mutiullah, Mutiullah (Journal of Islamic Thought and Philosophy, 2024)
From Greece to the contemporary era, democracy has become the main pillar of the global political system with its basic principle that power comes from the people, making democracy an ideal paradigm. As is well known, there is an impression that democracy has regressed. There are even claims that democracy is an illusion. This article aims to explain how Al-Farabi's socio-political philosophy can be integrated and applied concretely in the dynamics of democracy. The research approach uses qualitative theoretical analysis by referring to Al-Farabi's major works, especially "Al-Madina Al-Fadila." A review was conducted on contemporary journals and relevant literature. Research Findings This study identifies Al-Farabi's philosophical concepts, such as justice, moral leadership, and citizen participation, which have significant potential to shape social and political dynamics. The results provide an overview of the ethical values championed by Al-Farabi and are in line with the basic principles of democracy. The theoretical and practical implications of this research provide a strong impetus for critical reflection and constructive discussion regarding the implementation of democracy in the contemporary context.